Perancangan Sistem Informasi Manajemen Penerimaan Pesanan di PT Aulia Jaya Corp Berbasis Java - Dimas Amir Kusuma; V.H. Valentino; Rudi Prasetya (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2023)
Abstract— The purpose of this research is to design an Order Acceptance Management Information System, Case Study: PT Aulia Jaya Corp. In addition, the authors hope that users can understand the purpose of this system. The research method used is to use interviews and field observations. After that the authors designed, analyzed, and drew the conclusion that previously the Order Acceptance Management Information System at PT Aulia Jaya Corp was not always developing, so that by making this application program it could be used to facilitate work such as data input, orders and delivery, data search, and making reports to be more accurate. Keywords— Design, Information Systems, Stock, Orders, Delivery